The International and Political Journal: Competition in the Middle East and its impact on the balance of power in the region - Alwan, Prof Dr. Ibtsam Hataam (The International and Political Journal, 2024)
The Middle East region is one of the most important regions in the world and has the most resources and wealth. This geopolitical position that the Middle East region enjoys has made it a region of ambitions and desires for many great powers. Since human history, this region has witnessed many invasions and colonization for many years, and it was and still is a subject of ambitions for countries. Great, as after the end of the Cold War between the United States of America and the Soviet Union, a unipolar system emerged. In this system, a single power dominates the world, which is the United States of America, while Russia emerged as the heir to the Soviet Union, as the United States of America seeks to strengthen its presence in many regions of the world, especially in The Middle East is due to the geographical, economic and strategic importance of the Middle East to any international power seeking to control the world, while Russia seeks to revive Soviet influence in the Middle East region, specifically in the Fertile Crescent region (Syria - Iraq). This explains the intensification of Russian-American competition in the Middle East region .